Gender analysis in measurement materials: Critical thinking ability and science processing skills - Darmaji, Darmaji; Astalini, Astalini; Kurniawan, Dwi Agus; Rini, Endah Febri Setiya (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2022)
This study aims to determine whether there is a relationship and difference between science process skills and students' critical thinking skills based on gender. This type of research is descriptive quantitative research. The instruments used observation sheets and essay test questions. The sampling technique used was purposive sampling with samples of 90 students. The data analysis technique used by the researcher was descriptive statistics of Pearson Correlation and ANOVA tests. The results obtained were that the science process skills of students at SMPN 2 Batanghari were classified as good and dominated by female students with a percentage of 80.4%. Critical thinking skills were dominated by female students with a percentage of 32.6% (very critical). Then, there was a significant relationship between science process skills and students' critical thinking skills. Then, in the ANOVA test, male and female students' p-values of science process skills and critical thinking skills were less than 0.05. Therefore, there was a difference between the scientific process and the critical thinking skills of female and male students. This research is expected to contribute to schools and further research to improve learning methods that support critical thinking and science process skills.